Integrated Reporting as a Governance Mechanism: Evidence from Global Perspectives - Lestari, Dwirani Fauzi (Summa : Journal of Accounting and Tax, 2025)
Integrated reporting (IR) has emerged as a vital mechanism linking corporate governance with sustainability by integrating financial and non-financial information to enhance transparency, accountability, and long-term value creation. This study presents a narrative review examining the role of IR in strengthening governance structures by enhancing board oversight, improving risk management practices, and fostering stakeholder engagement across diverse contexts. A systematic methodology was employed, utilizing databases such as Scopus, Web of Science, and Google Scholar, with keywords including “integrated reporting,” “corporate governance,” and “stakeholder value.” Inclusion criteria focused on peer-reviewed studies published between 2010 and 2025 that investigated the interplay of IR, governance mechanisms, and organizational performance. The analysis synthesizes findings on seven key themes: the reduction of information asymmetry, governance mechanisms driving reporting quality, the role of board diversity and diligence, the influence of IR on tax avoidance and ethical governance, forward-looking disclosures in emerging markets, IR as a tool for stakeholder value creation, and the moderating effects of cultural and institutional factors. Results indicate that IR contributes significantly to financial efficiency, stakeholder trust, and ethical business practices, though adoption disparities persist between developed and developing economies. Systemic barriers such as resource limitations, cultural resistance, and weak regulation remain pressing challenges. Policy implications include the need for stricter regulatory frameworks, managerial training, and stronger internal audit systems. Future research should address causal pathways, develop standardized IR quality measures, and explore technological innovations. IR should be viewed as a cornerstone for sustainable governance and a strategic response to global stakeholder demands.